The Healthcare Future for the iGeneration: Integrating the Patient and the Healthcare System - Cathy H. Ficzere, PharmD, BCPS; Traci M. Poole, PharmD, BCACP; Rachel B. Franks, PharmD, BCACP; Elisa M. Greene, PharmD, BCACP; Kristina D. Wood, PharmD, BCACP; Philip E. Johnston, PharmD (University of Minnesota Libraries Publishing, 2013)
Objective: To propose a vision to integrate patients, their health-related data, and their wellness plans into the healthcare system using smartphone and tablet computer technology.Setting: Ambulatory care and community practicePractice Innovation: Utilization of smartphone and tablet computer technology to assess health care conditions, educate and involve patients, and facilitate seamless communication between the patient, electronic health record, pharmacy system, third-party payers, point-of-care testing, and all health-care providers.Main Outcome Measures: By providing integrated and customized information at the point of use, medication adherence and access to care will be increased and patients will engage in healthy behaviors more often resulting in an improved level of care for patients.Results: In the future, the authors believe if the vision is achieved, the health care system and patients will see improved health outcomes and more efficient utilization of the healthcare system.Conclusions: Our proposed use of technology provides an opportunity to empower patients to positively improve their own health which could be a vital advancement in health care, especially in the areas of medication adherence, improving access to care, and health behavior support. As pharmacists, we may also embrace technology opportunities to expand our roles as health care professionals as we continue to partner with patients and the health care team to improve outcomes.